The Right to Health as a Human Right in Access to Services for Marginalised Communities - Yuliati, Maulina (Law and Judicial Review, 2025)
Objective: This research aims to explores how to guarantee the right to health for marginalised groups, examines systemic barriers to accessing health services, and evaluates the role of government policies and health insurance programmes in reducing the healthcare gap. Research Design & Methods: This research uses a qualitative method with a literature review approach, where literature related to health rights and health insurance policies for marginalised groups are the main sources in analysing the problems and solutions. This approach allows for an in-depth understanding of the issues faced by marginalised groups in accessing health services as well as the role of government policies in addressing these disparities. Findings: The Indonesian government is obligated to ensure the right to health for all individuals, including marginalised groups, through an inclusive health system supported by legal frameworks and health insurance programmes like Health Social Security Administering Body (SSAB), JKN-KIS, and Prolanis, which help reduce disparities in access to health services. Implications & Recommendations: To reduce the health access gap, the government must develop inclusive policies, collaborate closely with community organizations, and prioritize infrastructure and resource distribution in remote areas to ensure equitable health services. Contribution & Value Added: This research emphasizes the importance of protecting the right to health for marginalised groups, the role of government in ensuring equal access through health policies, the need for a strong legal foundation, and offers practical recommendations for more inclusive and effective health policies.